A Contingent Approach to the Organization and Management of Public–Private Partnerships: An Empirical Study of English Health Care. (11th February 2013) - Waring, Justin; Currie, Graeme; Bishop, Simon
Abstract : Public–private partnerships (PPPs) have become a prominent feature of contemporary public policy. Although research shows variation in the contractual configuration of partnerships, there is little evidence of how these shape service and workforce organization. Through comparative ethnographic research on two PPP health care providers in the English National Health Service, this article develops the idea that PPPs exhibit "tight" and "loose" arrangements that relate to "downstream" service and workforce management. It induces four empirically grounded mediating factors to describe this relationship. The first relates to the "dependence" between partners in terms of financing, strategy, and resource sharing; the second to the "strategic orientation" of leaders; the third to the composition of the "professional workforce"; and the fourth to the "management approach" to service and workforce organization. The article contributes to the research literature by exploring the contingencies in how PPPs are operationalized on the ground .